1985
DOI: 10.2105/ajph.75.7.722
|View full text |Cite
|
Sign up to set email alerts
|

Public health aspects of mental health: the last 75 years of the American Journal of Public Health.

Abstract: The American Journal ofPublic Health has reflected the relationship of public health to the field of mental health over its 75-year history. The earliest volumes of the Journal addressed movements and concerns within public mental health. Quantitative analysis of mental health articles shows wide fluctuations over the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 127 publications
0
3
0
Order By: Relevance
“…Legal interventions developed from the 1600s to the present day have met with greater or lesser success, depending on the time and the context. These governmental measures have included the following legal tactics in regard to alcohol and drugs: import duties, taxes, control over production, control over distribution and sales, pharmacy laws (i.e., prescribing), anti‐smuggling initiatives, incarceration or other forms of punishment (for production, commerce, possession, and/or consumption of alcohol or drugs), propaganda, and mandatory treatment 24–27 . Application of these governmental measures, in various sequences, combinations, and levels of intensity, comprises the “statecraft” of addictions.…”
Section: Statecraft and Addictionmentioning
confidence: 99%
“…Legal interventions developed from the 1600s to the present day have met with greater or lesser success, depending on the time and the context. These governmental measures have included the following legal tactics in regard to alcohol and drugs: import duties, taxes, control over production, control over distribution and sales, pharmacy laws (i.e., prescribing), anti‐smuggling initiatives, incarceration or other forms of punishment (for production, commerce, possession, and/or consumption of alcohol or drugs), propaganda, and mandatory treatment 24–27 . Application of these governmental measures, in various sequences, combinations, and levels of intensity, comprises the “statecraft” of addictions.…”
Section: Statecraft and Addictionmentioning
confidence: 99%
“…Williams and Westermeyer have analysed these papers over the subsequent 75 years to show the fluctuations which they related to federal funding for mental health programmes (Fig. 4) (Williams & Westermeyer, 1985). The content of these articles is dominated by social issues, preventive measures, and, above all, by epidemiological research and its application to mental health services.…”
Section: Medicine -Neurologymentioning
confidence: 99%
“…In 1985, a review ‘Public health aspects of mental health—the last 75 years of the American Journal of Public Health ’, found that the earliest volumes of the Journal addressed movements and concerns within public mental health and concluded that the ‘Journal had played a unique and crucial role in the progress of public mental health’. 8 The Department of Health and Human Services (DHHS), USA in 1991 identified and listed ‘Mental Health and Mental Disorders’ as one of the eight priority areas for health promotion for the year 2000. 9 Across the Atlantic, in the United Kingdom, the situation is more equivocal.…”
mentioning
confidence: 99%